Contributions and challenges for worldwide vaccine safety: The Global Advisory Committee on Vaccine Safety at 15 years. Issue 29 (17th June 2016) - Asturias, Edwin J.; Wharton, Melinda; Pless, Robert; MacDonald, Noni E.; Chen, Robert T.; Andrews, Nicholas; Salisbury, David; Dodoo, Alexander N.; Hartigan-Go, Kenneth; Zuber, Patrick L.F.
Abstract: In 1999, the Global Advisory Committee on Vaccine Safety (GACVS) was established by the World Health Organization (WHO) to provide independent scientific advice on issues relating to the safety of vaccines and immunization. Fifteen years onward, we conducted a multi-faceted review to evaluate the impact, reach and challenges facing GACVS, including the role GACVS plays in informing global, regional and WHO member state vaccine policy. The methods included measures of organizational structure, citation impact, themes approached, and a discussion by previous and current members to evaluate past, present and future challenges. Given the increasing range of data sources and the deployment of many new vaccines, the Committee is facing the complex task of identifying the best available evidence for recommendations on vaccine safety. To help meet the increased demand for public transparency in decision making, GACVS-structured methodology for evidence-based decisions is evolving. GACVS also promotes best practices and capacity building for timely and accurate risk assessment; risk communications; outreach to help countries maintain and, if needed, rebuild public trust in vaccines; and advocacy for bridging the major gaps in vaccine safety capacity globally.